Model Polinomial Sebagai Model untuk Melihat Hubungan Fungsional Antara Variable Respond dan Perlakuan - Enny Supartini (Department of Statistics ITS, 2022)
The use of waste as raw material for other products is a good thing to do, one of which is the use of fish skin waste which can be used as raw material for making gelatin which is one of the raw materials that is widely used for food products. In the process of making gelatin, it is affected by the concentration of malic acid when soaking the fish skin raw material and it is necessary to know what concentration of malic acid is right to obtain the desired quality. To see the effect of malic acid content on the acidity of the yield, analysis of variance was used and to see the functional relationship between the quality of the acidity of the marinade and the concentration of malic acid given, a polynomial model could be used. From the results of the analysis, it was found that there was an effect of the concentration of malic acid given on marinade, while the functional relationship obtained was a polynomial second-order model.